Suposição de normalidade e gestão de risco: uma aplicação do var paramétrico via teste de aderência - Moralles, Herick Fernando; Sartoris Neto, Alexandre [UNESP]; Rebelatto, Daisy Aparecida do Nascimento (Associacao Brasileira de Engenharia de Producao - ABEPRO, 2014)
Given the weaknesses of the parametric VaR (Value-at-Risk) calculated by normality assumptions, this paper develops a method of parametric VaR calculation considering ten different probability distributions. Specifically, the distribution to be used for the VaR calculation of a specific asset or portfolio is indicated by the Kolmogorov-Smirnov goodness-of-fit test. Additionally, the study compares the normality assumptions applicability for the VaR calculation of both individual assets, and to a large portfolio, in the context of market stability. The experiment makes use of a sample of 15 individual assets traded in the Sao Paulo Stock Exchange and the IBOVESPA index, collected in the Economática® database. The goodness-of-fit tests and VaR calculations are performed by a program developed in MATLAB7.1®. This investigation demonstrates that the assumption of normality brings good risk estimates for large portfolios and individual assets.

Tendo em vista as fragilidades do VaR (Valor-em-Risco) paramétrico com pressuposto de normalidade, este trabalho desenvolve um método de cômputo do VaR paramétrico ajustado para dez diferentes distribuições de probabilidade. Especificamente, a distribuição a ser utilizada no cálculo do VaR para um dado ativo ou carteira é apontada pelo teste de aderência de Kolmogorov-Smirnov. Ainda, a investigação compara a aplicabilidade da suposição de normalidade para o cálculo do VaR para ativos individuais, e uma grande carteira, num contexto de estabilidade de mercados. O experimento realizado faz uso de uma amostra de 15 ativos individuais negociados na Bolsa de Valores de São Paulo, juntamente com o índice IBOVESPA, coletados na base Economática®. Os testes de aderência e os cálculos do VaR são realizados por um programa desenvolvido em MATLAB 7.1®. É encontrada uma grande ocorrência de ativos com boa aderência à distribuição Normal, demonstrando que o pressuposto de normalidade traz boas estimativas de risco tanto para um grande portfólio quanto para ativos individuais.
Normality assumptions and risk management: an application of the parametric var via goodness-of-fit test
Keywords: Parametric VaR (Value-at-Risk); Normality; Kolmogorov-Smirnov; VaR (Valor-em-Risco) paramétrico; Normalidade; Kolmogorov-Smirnov